PENGARUH BIMBINGAN KELOMPOK TERHADAP PENURUNAN MASALAH DALAM HUBUNGAN MUDA MUDI SISWA KELAS X SMK FARMASI IKASARI PEKANBARU T.P 2014/2015 - Adrine Liony; Rosmawati '; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Knowledge about the relationship young couple should be updated.Parents do sometimes forbid them to engage in a young relationship. But, they alwaysfind a loophole for dating in secret. The negative impact of these relationship arebecoming lazy student learning, academic achievement decline, unstable emotions andattitudes that tend temprament, be less focus on the future. Its all is a result ofmisundestranding them in running dating relationship. It will also have an impact ontheir social relationships with the environment. It would appear their indifference,because it it too focused on relationship. The guidance group aims to change theirperception of the relationship young couple, that the court does not have to negativelyimpact but many positive effects they should take from that relationship. So that theybetter understand how to maximize the positive impact of a young couple relationshipand minimize the negative impacts. After implemented the guidance of the group, andthe obtained result of research, it is know that the result of the count r can be a positiveand significant decrease in a relationship problems young couple before and after theguidance oh the group. This can be seen by comparing the count r with r table. Theresult is the count r > r table, so Ha is recieved. While the t test result can be seen pricet is greater than t table. (4,31>2,000), Ha is recieved. Wich means that there aresignificant defferences in the relationship problems before and after the group executedguidance.Key Words : minimize problem of relationship